Sociolinguistics Interdisciplinary Perspectives - Jiang, Xiaoming (IntechOpen, 2017)
This book gives an interdisciplinary perspective on how the language use is shaped by and evolves with human society and how in turn social activities are constructed by the way how language is organized and communicated. With a contribution from multiple neighboring scientific disciplines, this book characterizes fundamental mechanisms, represents wide applications, and introduces state-of-the-art approaches in the modern sociolinguistic research. Three unique questions are asked and addressed by eight independent chapters: (1) the diversity and dynamics of the language use in multilingualism, human development, and organizational change; (2) the application of linguistic analysis to society, policy planning, and health education; and (3) the new approaches to sociolinguistics with an emphasis on communicative and cognitive aspects of language use.